Impact of maternal physical activity on fetal breathing and body movement—A review. (March 2016) - Sussman, Dafna; Lye, Stephen J.; Wells, Greg D.
Abstract: Fetal movements, which include body and breathing movement, are important indicators of fetal well-being and nervous system development. These have been shown to be affected by intrauterine conditions. While maternal physical activity does induce a change in intrauterine conditions and physiology, its impact on fetal movements is still unclear. This paper will provide a brief review of the literature and outline the current knowledge with regards to the effects of maternal exercise on fetal body and breathing movements.